Synthetic Ligands of Olfactory Binding Proteins Modulate Aggregation Response of Asian Citrus Psyllid in the Presence of Host-Plant Volatiles - Patt, Joseph M.; Meikle, William G.; Niedz, Randall P.; Woods, Daniel (Frontiers in Plant Science, 2018)
There is interest in using ligands of chemosensory binding proteins (CBP) to augment an insect’s responsiveness to chemosensory cues. We showed previously that combining a synthetic ligand of a CBP with limonene enhanced the probing response of Asian citrus psyllid (Diaphorina citri). Here, we determined whether synthetic compounds, which were ligands of D. citri olfactory binding protein DCSAP4, influenced the settling and aggregation levels of psyllids on young citrus shoots. The shoots were presented either alone, with a seven-component mixture of citrus volatiles (‘Cmac scent’), or with different concentrations of test ligands. The test ligands and Cmac scent were dispensed from a droplet of an emulsified wax product (SPLAT). For each test, 200 D. citri were released in the test area and the numbers of psyllids on each sprig were counted 24 h later. Sprigs with ≥ 7 psyllids were considered to be an aggregation. A total of seven ligands were tested individually. Four of the ligands (654, 717, 784, and 861) modulated psyllid settling and aggregation response, causing greater settling and aggregation to sprigs presented with the Cmac scent than to those sprigs with blank SPLAT. Presentation of one of the ligands (019) resulted in an opposite effect in which psyllid settling and aggregation levels were lower on sprigs with Cmac scent than on those with blank SPLAT. There were no differences in settling levels in the different treatment vials in the Ligand 905 experiment. In the Ligand 937 experiment, settling levels did not vary significantly between treatment vials although settling levels were relatively high in all treatment vials and there was a significant treatment effect. Increased settling and aggregation levels were largely not observed with in the vials with only the test ligands, and there was little effect of ligand concentration on psyllid response levels. This suggests that the test ligands themselves did not attract the psyllids but rather modulated the psyllid’s response to the Cmac scent. The results suggest that synthetic ligands of D. citri CBPs can increase the effectiveness of citrus scent lures used to attract psyllids to monitoring traps and attract and kill devices.